Efficacy of exon-skipping therapy for DMD cardiomyopathy with mutations in actin binding domain 1 - Naoko Shiba; Xiao Yang; Mitsuto Sato; Shin Kadota; Yota Suzuki; Masahiro Agata; Kohei Nagamine; Masaki Izumi; Yusuke Honda; Tomoya Koganehira; Hideki Kobayashi; Hajime Ichimura; et al. (Elsevier, 2023)
Exon-skipping therapy is a promising treatment strategy for Duchenne muscular dystrophy (DMD), which is caused by loss-of-function mutations in the DMD gene encoding dystrophin, leading to progressive cardiomyopathy. In-frame deletion of exons 3-9 (Δ3-9), manifesting a very mild clinical phenotype, is a potential targeted reading frame for exon-skipping by targeting actin-binding domain 1 (ABD1); however, the efficacy of this approach for DMD cardiomyopathy remains uncertain. In this study, we compared three isogenic human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) expressing Δ3-9, frameshifting Δ3-7, or intact DMD. RNA sequencing revealed a resemblance in the expression patterns of mechano-transduction-related genes between Δ3-9 and wild-type samples. Furthermore, we observed similar electrophysiological properties between Δ3-9 and wild-type hiPSC-CMs; Δ3-7 hiPSC-CMs showed electrophysiological alterations with accelerated CaMKII activation. Consistently, Δ3-9 hiPSC-CMs expressed substantial internally truncated dystrophin protein, resulting in maintaining F-actin binding and desmin retention. Antisense oligonucleotides targeting exon 8 efficiently induced skipping exons 8-9 to restore functional dystrophin and electrophysiological parameters in Δ3-7 hiPSC-CMs, bringing the cell characteristics closer to those of Δ3-9 hiPSC-CMs. Collectively, exon-skipping targeting ABD1 to convert the reading frame to Δ3-9 may become a promising therapy for DMD cardiomyopathy.